Benign cystic lymphangioma of sigmoid mesocolon presenting as abdominal catastrophe: an extremely rare entity (Health Renaissance, 2015)
Mesenteric cystic lymphangiomas (MCLs) are uncommon benign cystic tumours of  unknown aetiology, most often seen in paediatric patients. The clinical presentation  ranges from an incidentally discovered abdominal cyst to symptoms of acute  abdomen. A10-year-old male presented with generalized abdominal pain, nausea  and vomiting & constipation of several hours duration. Emergency laparotomy  revealed multiple cystic masses along both the sides of sigmoid colon and mesocolon,  which were inflammed mimicking diverticulosis. Sigmoidectomy with colorectal  anastomosis was performed. The postoperative course was uncomplicated. MCLs  should be included in the differential diagnosis of cystic intra-abdominal lesions.  Even when asymptomatic and discovered incidentally, they must be treated surgically  because of the potential to grow, invade vital structures and develop life-threatening  complications.  Health Renaissance 2014;12(2): pp: 130-132